GENDER AND SOCIOECONOMIC DIFFERENCES IN BURNOUT AMONG EFL LEARNERS - Karolina, Venny; Buwono, Sri; Wiyono, Hadi; Septiana, Dita; Querioz, Carla; Xaixanith, Toby; Farhan, Firda Islamaya (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
This study examined burnout differences by gender and socioeconomic status among EFL university students in Indonesia (n=231,53.3%) , Laos (n=85, 19.5%), and Angola (n=117, 27%). Data from 433 students (females, n= 268, 61.89%, males, n=165, 38.11%) were collected using a cross-sectional survey, with participants recruited via WhatsApp groups shared by English lecturers. Burnout levels were measured using the Maslach Burnout Inventory-Student Survey (Schaufeli et al., 2002). The Mann-Whitney U Test showed that females (78.0%, median = 23.0) reported significantly higher burnout than males (67.3%, median = 22.0) (U = 18448, p = 0.004). This indicated that female students experienced more burnout than male students during their EFL learning. Regarding SES, similar percentages of students experienced moderate level of burnout: 75.6% from middle-to-upper and 72.1% from lower socioeconomic backgrounds. The Mann-Whitney U Test revealed no significant difference between these groups (U = 23389, p = 0.993, median for both groups= 22.0), indicating that burnout is common across socioeconomic statuses. To reduce burnout in EFL students, universities should offer engaging programs, like interactive games and stress-relief activities, focusing on the gender group with higher burnout, while incorporating fun English practice and time management tips.